Modernization theory revisited: latin america, europe, and the u.s. in the nineteenth and early twentieth century (2011)
Theories of modernization, globalization, and dependency have assigned a clear role to Latin America: the region has been seen as dependent, exploited, and institutionally weak. In these theories, modernization and globalization are seen as forces generated elsewhere; the region, in these views, has merely tried to “adjust” and “respond” to these external influences. At best, it has imitated some of the political institutions of the core countries and, most of the times, unsuccessfully. While there is very good empirical evidence that supports these views, the essay argues that these theories need some correction. Latin America has been an innovator and a modernizer in its own right, especially in its cutting-edge design of the nation-state and in its modern conceptualization of the national community. Thus, the essay suggests that the region has not merely “adjusted” to modernization and globalization. Rather, the paper makes a case for a reinterpretation of the region’s role as a modernizer and an important contributor to the consolidation of the modern West.